SUBSTANTIVE RATIONALITY IN COMMUNAL ECOVILLAGE MANAGEMENT - Guilherme Smaniotto Tres; Washington José de Souza (RAE: Revista de Administração de Empresas, 2022)
We approach elements of substantive rationality in administrative practice, in productive organizations, through attributes of communal management in agricultural production activities and care for natural and human life in ecovillages. Inspired by ethnography, we visited four ecovillages for 49 days, following daily life and working relationships. The results show that management routines emphasize social reproduction under principles of self-sufficiency. The sharing of land and the means of production and the orientation to collective care comprise an environment of social and economic security based on voluntary community bonds. Prevail management processes with a bias of substantive rationality that interconnect demands and ecological activism with actions to mitigate ecological degradation and enhance the diversity of life, characterizing traces of human emancipatory administrative practices in the productive sphere in private organizations.